Meningkatkan Keterampilan Menulis Teks Puisi Melalui Melalui Metode Outdoor Study - Dewi Nurani, Warsiman Alisiananda (Balai Diklat Keagamaan Surabaya, 2020)
Poetry writing, as one of learning activities which is thought by teacher, need to be re-evaluated. Thetraditional learning method that limits students creativity must be removed. This research aims to upgradethe poetry writing skill through outdoor study method that takes a month of period. The researcher usesClassroom Action Research (CAR) and processes the data quantitatively. The result of the research shows thatthe poetry writing skill of students increase as time goes by. It can be seen from the first cycle that has74.39% to be 86.25% in the second cycle. As well as the students writing skill, it also increases the resultof teacher and student activity that is observed. The percentage of teacher activity increases from 86.60 %in the first cycle to be 93.75 % in the second cycle, meanwhile the student activity increases from 84.08 %in the first cycle to be 89.28 % in the second cycle. From these results, it can be concluded that outdoorstudy as the method of learning, increases students writing skill especially for poetry writing.